Analyse d’erreurs lexicales d’apprenants du FLS : démarche empirique pour l’élaboration d’un dictionnaire d’apprentissage - Hamel, Marie-Josée; Milicevic, Jasmina (Canadian Journal of Applied Linguistics, 2007)
This article deals with lexical errors, i.e., errors stemming from an insufficient knowledge of properties—semantic, formal and combinatorial—of lexical units. Such errors are frequent in written texts produced by language learners. They indicate that there are gaps to be filled in the learner’s lexical knowledge, in particular, when it comes to learners’ ability to efficiently use lexical and paraphrastic relations in text production. Our analysis of a corpus of texts produced by learners of French as a second language, based on a typology of lexical errors we have developed, has revealed a high number of lexical errors, in particular those involving meaning properties of lexical units and their restricted lexical cooccurrence properties. These findings will be used for the development of a learners’ dictionary based on the Meaning-Text linguistic theory and designed in such a way as to facilitate the acquisition and active use of lexical and paraphrastic relations.